2015
DOI: 10.1038/mt.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the Adhesion Cascade at the Premetastatic Niche for Prevention of Breast Cancer Metastasis

Abstract: Shear-resistant adhesion and extravasation of disseminated cancer cells at the target organ is a crucial step in hematogenous metastasis. We found that the vascular adhesion molecule E-selectin preferentially promoted the shear-resistant adhesion and transendothelial migration of the estrogen receptor (ER)(-)/CD44(+) hormone-independent breast cancer cells, but not of the ER(+)/CD44(-/low) hormone-dependent breast cancer cells. Coincidentally, CD44(+) breast cancer cells were abundant in metastatic lung and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…The aptamer technology has been most successfully applied in the field of cancer biology, where aptamers have been able to identify phenotypic variations between cell types, representing differences in molecular signatures [13,14]. We have shown that aptamers can safely target and reduce cancer metastasis [15][16][17], can be easily selected against tissues using a laser microdissection method [9], and enhance binding of liposomes and nanoparticles [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The aptamer technology has been most successfully applied in the field of cancer biology, where aptamers have been able to identify phenotypic variations between cell types, representing differences in molecular signatures [13,14]. We have shown that aptamers can safely target and reduce cancer metastasis [15][16][17], can be easily selected against tissues using a laser microdissection method [9], and enhance binding of liposomes and nanoparticles [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with a previous report that breast cancer could metastasize to distant organs through a hematogenous route. 29 Also, we found that inflammatory cell (neutrophils, yellow dotted circle) invasion was remarkable in the control group. As we know, inflammation is associated with cancer metastasis.…”
mentioning
confidence: 66%
“…Filopodia then dynamically extends and retracts into the parenchyma as cells migrate to a perivascular position [46,48]. Mediators of this process include specific adhesion molecules and proteases (e.g., integrins α5, β1, β3, cathepsin-S, matrix metalloproteinases (MMPs), and E-selectin [47,[49][50][51][52][53] retracts into the parenchyma as cells migrate to a perivascular position [46,48]. Mediators of this process include specific adhesion molecules and proteases (e.g., integrins α5, β1, β3, cathepsin-S, matrix metalloproteinases (MMPs), and E-selectin [47,[49][50][51][52][53]).…”
Section: Microenvironment-driven Selection Pressurementioning
confidence: 99%
“…Mediators of this process include specific adhesion molecules and proteases (e.g., integrins α5, β1, β3, cathepsin-S, matrix metalloproteinases (MMPs), and E-selectin [47,[49][50][51][52][53] retracts into the parenchyma as cells migrate to a perivascular position [46,48]. Mediators of this process include specific adhesion molecules and proteases (e.g., integrins α5, β1, β3, cathepsin-S, matrix metalloproteinases (MMPs), and E-selectin [47,[49][50][51][52][53]). The perivascular niche (PVN) is another critical point of tumour cell attrition-most are unable to tolerate the neuroinflammatory reaction that is rapidly instigated by microglia and astrocytes [28,45,48,[54][55][56][57][58][59][60][61].…”
Section: Microenvironment-driven Selection Pressurementioning
confidence: 99%